Unicentric Castleman's disease: an uncommon cause of posterior mediastinal mass - Alavi, Aliasghar (BMJ Publishing Group, 2013)
Castleman's disease is a rare lymphoproliferative disease that may be unicentric or multicentric in presentation. It may develop anywhere along with the lymphatic system such as the abdomen, neck and thoracic cavity. However, mediastinum is the most common location for unicentric disease. Here, we discuss a unicentric Castleman's disease in a 28-year-old woman who presented with cough, mild dysphagia and a large posterior mediastinal mass.